Developing live skill and building youth leadership trough sport - Juhrodin Juhrodin; Goesti Sabda Laksana (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2022)
Youth has a strategic role in national development, as the successor to the sustainability and progress of the nation, youth are required to participate in various experiences in order to enrich their abilities and skills as provisions in the future. The real challenges faced by youth in this century are no less complicated than those before and after independence, because the challenges they face are global, as is the case with the current pandemic. This research aims to find opportunities and opportunities for youth to become productive, successful, innovative, and independent youth. The main topics in this research are Positive Youth Development, Leadership, Lifeskills and Sports. The research method used is Literature Review or literature review sourced from articles in reputable or accredited journals, which are related to the research topic. Articles that are referenced are articles that have been published from 2000 to 2022 which are searched on the Elsevier, Francis and Taylor Online database, Google Scholar in this review. The results of the literature review are then reviewed, analyzed and finally synthesized the results.Key word:  Lifeskill,  Postive Yout Development , Leadership Sport